Protective role of engineered extracellular vesicles loaded quercetin nanoparticles as anti-viral therapy against SARS-CoV-2 infection: A prospective review - Raghav, Alok; Giri, Richa; Agarwal, Saurabh; Kala, Sanjay; Jeong, Goo-Bo- (Frontiers in Immunology, 2022)
Quercetin (QCT) is a naturally occurring phenolic flavonoid compound with inbuilt characteristics of antioxidant, anti-inflammatory, and immune protection. Several recent studies have shown that QCT and its nanoparticles have therapeutic potential against severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection. Novel therapeutics also include the implication of extracellular vesicles (EVs) to protect from SARS-CoV-2 viral infection. This article highlighted the therapeutic/prophylactic potential of engineered EVs loaded with QCT against SARS-CoV-2 infection. Several biotechnological engineering approaches are available to deliver EVs loaded with QCT nanoparticles. Among these biotechnological advances, a specific approach with significantly higher efficiency and yield has to be opted to fabricate such drug delivery of nano molecules, especially to combat SARS-CoV-2 infection. The current treatment regime protects the human body from virus infection but has some limitations including drugs and long-term steroid side effects. However, the vaccine strategy is somehow effective in inhibiting the spread of coronavirus disease-19 (COVID-19) infection. Moreover, the proposed exosomal therapy met the current need to repair the damaged tissue along with inhibition of COVID-19-associated complications at the tissue level. These scientific findings expand the possibilities and predictability of developing a novel and cost-effective therapeutic approach that combines the dual molecule, EVs and QCT nanoparticles, to treat SARS-CoV-2 infection. Therefore, the most suitable engineering method to fabricate such a drug delivery system should be better understood before developing novel therapeutics for clinical purposes.